2020
DOI: 10.1038/s41598-020-70213-9
|View full text |Cite
|
Sign up to set email alerts
|

The BXD21/TyJ recombinant inbred strain as a model for innate inflammatory response in distinct brain regions

Abstract: Oxidative stress and inflammatory cytokines affect the human brain, increasing the risk for mood and cognitive disorders. Such risk might be selective to brain-specific regions. Here, we determined whether BXD recombinant inbred (RI) mice strains are more suitable than C57BL/6J mice for the understanding of the relationship between antioxidant response and inflammatory responses. We hypothesized that inflammatory responses could be independent of antioxidant response and be inherent to brain-specific regions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…It has been shown that exposure to oxidized soybean oil after a high oxidized diet results in oxidative stress in the intestinal mucosa (Liang et al, 2015). Sustained oxidative stress may result in the altered expression of certain genes involved in inflammatory pathways (Liu et al, 2021; López‐Granero et al, 2020). It was also confirmed in the present study that maternal feeding of oxidized soybean oil during late gestation and lactation resulted in abnormal mRNA levels of inflammatory‐regulating cytokines in the jejunum of the offspring.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that exposure to oxidized soybean oil after a high oxidized diet results in oxidative stress in the intestinal mucosa (Liang et al, 2015). Sustained oxidative stress may result in the altered expression of certain genes involved in inflammatory pathways (Liu et al, 2021; López‐Granero et al, 2020). It was also confirmed in the present study that maternal feeding of oxidized soybean oil during late gestation and lactation resulted in abnormal mRNA levels of inflammatory‐regulating cytokines in the jejunum of the offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Phillips et al (1995) studied male BXD RI strains upon acute and repeated dosing with 2 g/kg ethanol. The authors found that both acute and repeated treatments led to changes in the initial ethanol response, which was attributed to the sensitization of locomotor stimulation; QTL analyses demonstrated an association with basal locomotor activity and acute locomotor response on chromosomes 3,4,7,11,12,13,15, and 17 to initial ethanol response [31]. Likewise, a study with 20 BXD RI murine strains and C57BL/6J and DBA/2J progenitor strains exposed to 2 g/kg of ethanol evaluated ethanol's ability to induce conditioned place preference, noting a significant association between ethanol-seeking behavior in BXD RI mice and genetic markers on chromosomes 4, 8, 9, 18 and 19 [32].…”
Section: Ethanolmentioning
confidence: 99%
“…More recently, thanks to progress in genomic sequencing [ 5 ], the BXD RI mice were used to map complex traits. This advance has led to the use of BXD RI mice in addressing neurotoxicology and neurodegeneration [ 6 , 7 ]. Specifically, the relevance of the BXD RI family has been extended to the analysis of the genetics of behavioral phenotypes, including alcohol and drug addiction [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ], neurodegenerative processes [ 4 , 6 , 15 , 16 , 17 ], heavy metals and pesticides [ 3 , 18 , 19 ], and changes related to the degeneration of the visual system [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation